Answer:
I hope it will helps u
Explanation:
As given
x²-3x-10
Now according to the one of the rule of factorization ,
we have to find such two values whose product becomes equal to the
"product of first and last term " and if we sum those numbers it should be equal to the "middle term of it".
so such numbers are -5x and +2x
if we add or multiply them we get the above
as adding -5x+2x=-3x (middle term)
also multiplying -5x*2x=-10x² (product of 1st and last term)
so now , we can write as,
x²-3x-10
=x²-5x+2x-10
now making groups of 2 terms,
=(x²-5x)+(2x-10)
now common
=x(x-5)+2(x-5)
now common(x-5)
=(x-5)(x+2) This is the required factors.....